MEMPERKUAT IDENTITAS GENERASI BUDDHIS YANG UNGGUL BERLANDASKAN NILAI-NILAI BUDDHAYANA (BUDDHIS CAMP PEMUDA BUDDHAYANA SEPROVINSI NTB) - RAPIADI, RAPIADI; SENERU, WISTINA; SAPUTRI, VIKE APRILIANIN MARWINTARIA; PANNA, PANNA; KRISTIANTO, ADI (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Buddhist Camp activities for Buddhayana youth throughout NTB Province which will be held on 07–09 April 2023 at Vihara Jaya Wijya, North Lombok, West Nusa Tenggara, carry the theme "Strengthening the Identity of a Superior Buddhist Generation Based on Buddhayana Values". This theme was chosen because the young generation of Buddhists is the hope for the future of Buddhism. Buddhayana Youth Buddhist Camp throughout NTB Province is an activity that aims to strengthen the identity of a superior Buddhist generation based on Buddhayana values. carried out through a series of activities, such as Dharma classes, group discussions, and meditation. Participants are given a deep understanding of Buddhist teachings and empowered to apply them in everyday life. The result is young people who are more connected to religious values and are able to use Buddhayana as a moral foundation in their actions. Buddhist Camp participants are also given the opportunity to develop themselves through various activities, such as mindfulness and art. These activities can help participants to better understand themselves and their potential. Buddhist Camp participants are encouraged to practice Buddhist teachings in their daily lives. ABSTRAKKegiatan Buddhis Camp pemuda buddhayana se-Provinsi NTB yang diselenggarakan pada tanggal 07–09 April 2023 di Vihara jaya Wijya Lombok Utara, Nusa Tenggara Barat, mengusung tema "Memperkuat Identitas Generasi Buddhis yang Unggul Berlandaskan Nilai-Nilai Buddhayana". Tema ini dipilih karena generasi muda Buddhis merupakan harapan masa depan agama Buddha. Buddhis Camp Pemuda Buddhayana se-Provinsi NTB merupakan sebuah kegiatan yang bertujuan untuk memperkuat identitas generasi Buddhis yang unggul dengan landasan pada nilai-nilai Buddhayana. dilakukan melalui serangkaian kegiatan, seperti kelas Dharma, diskusi kelompok, dan meditasi. Peserta diberikan pemahaman mendalam terhadap ajaran Buddha dan diberdayakan untuk mengaplikasikannya dalam kehidupan sehari-hari. Hasilnya adalah pemuda yang lebih terkoneksi dengan nilai-nilai agama dan mampu menjadikan Buddhayana sebagai landasan moral dalam tindakan mereka.Peserta Buddhis Camp juga diberikan kesempatan untuk mengembangkan diri melalui berbagai kegiatan, seperti mindfulness, dan seni. Kegiatan-kegiatan tersebut dapat membantu peserta untuk lebih memahami diri sendiri dan potensinya.Peserta Buddhis Camp didorong untuk mempraktikkan ajaran Buddha dalam kehidupan sehari-hari.